The foreign policy of the Republic of Belarus: yesterday, today, tomorrow - Antonovich, Ivan I. (Journal of the Belarusian State University. Sociology, 2019)
My assessment of the world political strategy shows that new type of wars begun in the XXI century never finish with victory. They leave countries in ruins without hope for a better future. It is my estimate that the present situation in the world faces two ways threats: world terrorism and the crisis of democracy. The author shows his assurance that world terrorist threat can be overcome only through international solidarity which remains elusive, the crisis of democracy can only be overcome through basis reforms for which the countries today are not ready. Belarus is developing its sovereign external policy taking due attention to the contradictions of the modern world. Its global priorities dictate it close co-operation with the Russian Federation, Eurasian community, Atlantic community, bilateral and multilateral co-operation with European countries on the basis of mutual respect and commonalty of interest.